In Search of Community in Rural China. Issue 1 (27th July 2020) - Hill, Ann Maxwell; Wei, Jinji; Rose, Susan
Abstract : Change in China's urban areas is dramatic, as cityscapes emerge from rice paddies. China's rural areas reflect the impact of globalization, especially as villagers leave home for work in towns and cities. Much of the current research on migration out of China's countryside has noted its negative consequences for village life, a phenomenon often dubbed "hollowing out." Our qualitative research on "hollowing out, " undertaken by a student-faculty team from Dickinson College, focused on village sustainability in an area that has experienced substantial out-migration. Given the time constraints of our funding, we concentrated on village activities that were by and large public and observable – farm ecology and local culture. The village "stay-behinds" did most of the community's agricultural labor and cultural work, the latter especially manifest in religious activities. Based on a combination of fieldwork and available published materials, we found evidence for optimism about the sustainability of the village community in the age of migration.